Access mechanism of TMP under mobile network - WU Zhen-qiang; ZHOU Yan-wei; QIAO Zi-rui (Tongxin xuebao)
The publication of TCG MTM standard ensured the safety of mobile terminal and its promotion results in the changes of communication on mobile terminals.An access mechanism to trusted mobile platform（mobile terminals with MTM chips,TMP） was proposed on mobile Internet.This mechanism defined an extended service set as a service field,introduced TMP and Internet ISP of strategy decider management field,and defined two visit mode of TMP on mobile Internet,self field service and cross field visit.The progress of each mode was described in details.Cross field visit mode was defined as roaming service and resource request.The trusted evaluation system of TMP access mechanism was specifically described.Universal combinational safe mode was used to analyze the safety of the two TMP access.The analysis shows that this mechanism brings about trusted TMP access on mobile Internet and is safe,practical and high efficient.